ChemInform Abstract: An Efficient Synthesis of Bis‐1, 3‐(3′‐aryl‐N‐heterocycl‐1′‐yl)arenes as CCC‐NHC Pincer Ligand Precursors. Issue 46 (18th November 2014) - Howell, Tyler O.; Huckaba, Aron J.; Hollis, T. Keith
Abstract CCC‐NHC pincer ligands are prepared from bisimidazoles and bis(aryl)iodonium salts.